Media Convergence-Deconvergence-Coexistence Triad in Indonesia: The Case of Liputan6.com - Putut Widjanarko; Lita Hariyani (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2022)
Media convergence, the dominant perspective to understanding the recent intertwining development of media and digital technologies, has been criticized for not reflecting the phenomenon of the current media landscape. The convergence-deconvergence-coexistence triad is proposed as the better framework to understand such phenomenon. Therefore, this article implements this triadic interaction to analyze the evolution of Liputan6.com, one of the most prominent online news media in Indonesia. This study employs in-depth interviews, observation, and document/archive analysis. This study identifies three periods of development of Liputan6.com since its establishment in 2000, and each period has different relation dynamics of the three aspects within the triad framework. By applying the convergence-deconvergence-coexistence triadic perspective, this article offers a multifaceted and multilayer analysis of the evolution of online news media such as Liputan6.com.